Mapping Presence: An Exploration of Embodiment and Knowledge Transfers in Cyber-Mediated Classrooms (LEARNing Landscapes, 2022)
As teachers and students navigated the forced transition to online education, their physical and social interaction became possible only through technology. How did this mediated interaction affect learning outcomes, teacher presence, and their performance, in synchronous classroom spaces? What was lost in the translation of in-person instruction? What might this lost element tell us about the epistemology of embodiment, the transfer of knowledge in the classroom, and the roles of teachers and students within these knowledge frameworks? Through autoethnographical performative inquiry, this paper argues that embodiment—individual and collective—and multidimensional proximity construct sites of knowledge transfer.
Keywords: pedagogy; dimensionality; mediation; embodiment; delivery